A comparison of Mesua ferrea L. and Hura crepitans L. for shade creation and radiation modification in improving thermal comfort - Shahidan, Mohd Fairuz; Mohd Shariff, Mustafa Kamal; Jones, Philip; Salleh, Elias; Abdullah, Ahmad Makmom (Elsevier B. V., 2010)
Open spaces in tropical climates are highly exposed to solar radiation. These conditions will influence the outdoor energy budget, leading to an increased heat island effect and reduced human thermal comfort. Trees, however, can influence the microclimate through radiation control that indirectly reduces direct radiation uptake and glare by humans and buildings. This condition affects building energy budget and human thermal comfort. This study compares the effectiveness of Mesua ferrea L. and Hura crepitans L. in shade creation and radiation modification in improving human thermal comfort. The study employed two methods: (i) a field measurement procedure and (ii) a computer-based sun-shading analysis using ECO-TECT. The results from this study indicate that both M. ferrea L. and H. crepitans L. contribute significantly to direct thermal radiation modification below their canopies. The average solar filtration under the tree canopy for M. ferrea L. was 93%, with 5% canopy transmissivity, 6.1% of leaf area index (LAI) and 35% of shade area. For H. crepitans L. the average heat filtration under the canopy was 79%, with transmissivity of 22%, LAI of 1.5 and 52% of shade area. Thus, the study found that M. ferrea L. was more significant as a thermal radiation filter than H. crepitans L., due to the former's denser foliage cover and branching habit. This significant filtration capability contributes to reduce more terrestrial radiation, cooling the ground surfaces by promoting more latent heat, reducing air temperature by promoting more evapotranspiration and effectively improves outdoor thermal comfort in tropical open spaces.